Study of Monoethanolamine Nitrate Content Reduction in Explosive Slurries - Carini, V. P.; Carvalho, J. A. [UNESP]; Castro, J. N. C. [UNESP]; Bastos-Netto, D. (Abcm Brazilian Soc Mechanical Sciences & Engineering, 2010)
The reduction of the fuel content of a monoethanolamine nitrate (MEAN) fueled explosive slurry was investigated. The work was performed in three phases. The first one involved the MEAN content reduction in a reference slurry from its initial value of 36 down to 24% by weight, the balance being filled with ammonium nitrate, the least expensive item in the slurry composition. This proved to be successful, leading to an overall cost reduction of 17%, while keeping the overall performance quite satisfactory. The second phase consisted in trying to bring the MEAN content down from 24 to 17%. Although this led to further cost reduction, the formulations, obtained by substituting part of the MEAN content by ammonium nitrate/fuel oil (ANFO), produced unsatisfactory results regarding ignition and densities. In the third phase, the Design of Experiments Technique was used to find formulations displaying not only lower cost, but also acceptable overall performance. This led to a raw material cost reduction ranging from 23 to 26% relative to the initial reference slurry formulation.
Keywords: explosive slurries; monoethanolamine nitrate (MEAN); explosive cost and performance